Isolation and characterization of antimicrobial compound from Chromolaena odorata - Prakash1; S. K. Fathima2*, S. L. Sukanya1,2, J. Sudisha1, H. S. (Journal of Phytology, 2011)
Solvents such as methanol, ethanol, ethyl acetate, hexane and chloroform with extracts of Chromolaena odorata were tested against clinical bacteria (Escherichia coli and Staphylococcus aureus) and phytopathogenic bacteria (Xanthomonas vesicatoria and Ralstonia solanacearum). Among treatments, maximum In vitro inhibition was scored in methanol extracts of C. odorata which offered inhibition zone of 8mm, 7mm, 5mm and 7mm against tested bacteria E. coli, S. aureus, X. vesicatoria and R. solanaccearum, respectively. Further, ethyl-acetate and hexane extracts of C. odorata on TLC produced 9 spots with varied level of inhibition. Partially purified compound from TLC (band 2) showed maximum inhibition against tested bacteria. The promising anti-microbial compound from ethyl-acetate and hexane extracts (5:5) of C. odorata was further purified using column chromatography which recorded 11mm, 10mm, 9mm and 7mm against E. coli, S. aureus, X. vesicatoria and R. solanaccearum, respectively. The minimum inhibitory concentration (MIC) value for clinical bacteria was ranged between 0.35 to 4.0 mg/ml and 0.25 to 4.0 mg/ml for phytopathogenic bacteria. HPLC chromatogram showed only one peak, where the retention time was 21.775 min. Structure of the anti-microbial compound was determined by Fourier Transform Infrared Spectra (FTIR) and 2D nuclear magnetic resonance (NMR) and liquid chromatography mass spectra (LC-MS). The structure of anti-microbial compound found to be phenolic groups. LC-MS spectrum of methanolic extract of C. odorata compound exhibiting intense peak at m/z 301.3109 and the molecular weight of the compound was probably m/z 437.4129.